Effects of a whole food diet on immune function and inflammatory phenotype in healthy dogs: A randomized, open-labeled, cross-over clinical trial - Jaffey, Jared A.; Su, Dan; Monasky, Ross; Hanratty, Brenna; Flannery, Elizabeth; Horman, Melissa (Frontiers in Veterinary Science, 2022)
Whole foods in humans decrease inflammation and risk for various diseases, as well as increase weight loss and immune function. Nutrition has been shown to be an integral component in the management of various diseases in dogs but the immunologic and anti-inflammatory effects of whole food diets have not been explored. Therefore, our objective was to assess the effect of feeding a whole food diet on immune function and inflammatory phenotype in healthy dogs. A prospective, randomized, open-labeled, cross-over clinical trial was performed. Sixteen healthy client-owned dogs were fed either a whole food or an extruded dry diet, and after 67 days, they were fed the alternate diet for an additional 67 days. Blood samples were obtained at the completion of each treatment arm (i.e., days 67 and 134). Serum c-reactive protein (CRP), haptoglobin (Hp), and serum amyloid-A (SAA) were measured with ELISA assays. Whole blood cultures were performed with exposure to a phosphate-buffered solution (PBS), lipopolysaccharide (LPS), and lipoteichoic acid (LTA). A canine specific multiplex bead-based assay was then used to measure tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-10, granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-2, IL-8, and monocyte chemoattractant protein (MCP)-1 concentrations. Granulocyte/monocyte (GM) phagocytosis and oxidative burst associated with Escherichia coli were evaluated via flow cytometry. Dogs fed a whole food diet had significantly lower TNF-α-to-IL-10 ratios (P = 0.05) and higher production of IL-8 (P = 0.03) with LTA-exposed leukocytes compared to dogs fed an extruded dry diet. There were no between-treatment differences in the remaining leukocyte cytokine responses, serum CRP, Hp, SAA concentrations, or GM phagocytic and oxidative burst capacities. Whole food diets could have immunomodulatory effects in dogs. Future studies in non-healthy dogs are warranted.